2015
DOI: 10.1155/2015/313021
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Lipoic Acid on Selected Cardiovascular Diseases Caused by Age-Related Oxidative Stress

Abstract: Oxidative stress is considered to be the primary cause of many cardiovascular diseases, including endothelial dysfunction in atherosclerosis and ischemic heart disease, hypertension, and heart failure. Oxidative stress increases during the aging process, resulting in either increased reactive oxygen species (ROS) production or decreased antioxidant defense. The increase in the incidence of cardiovascular disease is directly related to age. Aging is also associated with oxidative stress, which in turn leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 122 publications
1
44
0
2
Order By: Relevance
“…Not only does this product contain the typical components of cereals but also after fermentation it is enriched in bioactive substances such as phenolic components and alpha-lipoic acid [13], a natural antioxidant that can provide protection against reactive oxygen species- (ROS-) induced vascular damage [14]. In healthy rabbits, LG improves lipid profile and antioxidant status [15], while in in vitro studies LG has been shown to exert protective effects in human microvascular endothelial cells exposed to oxidized-LDL controlling both oxidative and inflammatory processes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Not only does this product contain the typical components of cereals but also after fermentation it is enriched in bioactive substances such as phenolic components and alpha-lipoic acid [13], a natural antioxidant that can provide protection against reactive oxygen species- (ROS-) induced vascular damage [14]. In healthy rabbits, LG improves lipid profile and antioxidant status [15], while in in vitro studies LG has been shown to exert protective effects in human microvascular endothelial cells exposed to oxidized-LDL controlling both oxidative and inflammatory processes [16].…”
Section: Introductionmentioning
confidence: 99%
“…α‐Lipoic acid (LA) is an organosulphur compound derived from octanoic acid. Because of their unique characteristics to work both in hydrophilic and lipophilic environments, LA and its reduced form dihydrolipoic acid (DHLA) have gained considerable attention as biological thiol antioxidants, which are central to antioxidant defense in nervous system tissues …”
Section: Introductionmentioning
confidence: 99%
“…The cytoprotective effect of ALA is derived from its ability to limit the generation of reactive oxygen species, by inhibiting NADPH and xanthine oxidase and by effectively activating the PI3k/Akt pathway and related proteins [26]. In addition, Skibska and Goraca [8], reported that thioredoxin (Trx), a redox signaling molecule similar to HO-1 and Nrf2, which are highly regulated during oxidative stress (hypoxia), is upregulated in ALA-treated rats and indirectly activates antioxidant expression. Our results are also in agreement with those of Turamanlar and colleagues [27], who reported that in rats with sciatic nerve ischemic injury the elevated MDA, SOD, GSH peroxidase, and GSH levels revert to normal in response to ALA. Oxidative stress and inflammation are interlinked responses.…”
Section: Discussionmentioning
confidence: 99%
“…ALA has two sulfhydryl (thiol) groups and a free hydroxyl group that act as electron donors and account for the free-radical scavenging activity of ALA [7]. In addition, ALA exhibits metal-chelating activity and is an essential cofactor for enzymes involved in the Krebs cycle and the electron transport chain [8]. ALA also increases (regenerates) glutathione (GSH), thereby maintaining optimal levels of other antioxidants, such as vitamins C and E, superoxide (SOD), and catalase (CAT) [9].…”
Section: Introductionmentioning
confidence: 99%